Lessons from the steel industry: if you can't compete on price, innovate your way to value-added differentiation. Issue 5 (18th September 2017) - Blitz, Amy
Abstract : Purpose: Threats from low cost competitors are a fact of markets, a trend likely not just to continue in coming years but to accelerate. The fundamental strategic question the authors consider is how best to compete when competing on price alone is not a realistic option. Design/methodology/approach: This case details how Korea's POSCO steel company has successfully pivoted from competing on price to competing on innovation. Findings: POSCO introduced new revenue-generating offerings as well as innovative cost-saving processes while also improving its environmental footprint. Practical implications: POSCO began sending engineers to work directly with customers to identify areas of opportunity for specialized, differentiated, high value added steel products. Originality/value: This case shows how POSCO managed to identify and address a host of unmet customer needs, introducing new revenue-generating offerings as well as cost-saving new processes while also improving the company's environmental footprint, making it a desirable partner for customers concerned about having a socially responsible supply chain.